Wiedza kobiet, studentek pielęgniarstwa, na temat profilaktyki raka piersi = Knowledge of women, female students of nursing, on prevention of breast cancer - Szadowska-Szlachetka, Zdzisława; Baczewska, Bożena; Kulbaka, Zuzanna; Muraczyńska, Bożena; Kropornicka, Beata; Dzirba, Alina; Łuczyk, Robert (Journal of Education, Health and Sport, 2016)
Szadowska-Szlachetka Zdzisława, Baczewska Bożena, Kulbaka Zuzanna, Muraczyńska Bożena, Kropornicka Beata, Dzirba Alina, Łuczyk Robert. Wiedza kobiet, studentek pielęgniarstwa, na temat profilaktyki raka piersi = Knowledge of women, female students of nursing, on prevention of breast cancer. Journal of Education, Health and Sport. 2016;6(12):504-519. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.209525 http://ojs.ukw.edu.pl/index.php/johs/article/view/4080 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 19.12.2016. Wiedza kobiet, studentek pielęgniarstwa, na temat profilaktyki raka piersi Knowledge of women, female students of nursing, on prevention of breast cancer Zdzisława Szadowska-Szlachetka1, Bożena Baczewska2, Zuzanna Kulbaka, Bożena Muraczyńska3, Beata Kropornicka2, Alina Dzirba4, Robert Łuczyk2 1Zakład Onkologii - Katedra Onkologii i Środowiskowej Opieki Zdrowotnej. Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2Katedra Interny z Zakładem Pielęgniarstwa Internistycznego. Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 3Katedra Chirurgii i Pielęgniarstwa Chirurgicznego. Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 4Zakład Ratownictwa Medycznego. Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Streszczenie Wstęp: Choroby nowotworowe – zarówno w Polsce, jak i na świecie stanowią poważny problem ze względu na ich rozpowszechnienie. Co roku na nowotwór złośliwy piersi w Polsce choruje coraz większa liczba kobiet i zgodnie z danymi Krajowego Rejestru Nowotworów w ciągu ostatnich trzech dekad zachorowalność na ten rodzaj nowotworu wzrosła ponad dwukrotnie. Pierwotna profilaktyka raka piersi opiera się przede wszystkim na podnoszeniu świadomości prozdrowotnej dotyczącej udowodnionych naukowo czynników ryzyka zachorowania na raka piersi. Celem pracy była ocena stanu wiedzy kobiet, studentek pielęgniarstwa, na temat profilaktyki raka piersi. Materiał i metoda: Badania przeprowadzono na Wydziale Nauk o Zdrowiu UM w Lublinie. Łącznie objęto 147 kobiet, studentek kierunku pielęgniarstwo, I i II stopnia. W badaniach posłużono się metodą sondażu diagnostycznego. Materiał badawczy zebrano za pomocą techniki wywiadu, przy użyciu kwestionariusza ankiety własnego autorstwa, skonstruowany w oparciu o przegląd aktualnego piśmiennictwa. Analizę statystyczną zebranego materiału przeprowadzono w pakiecie Statistica 10.0. StatSoft. Wnioski: Znajomość czynników ryzyka i objawów raka piersi wśród kobiet, studentek pielęgniarstwa, jest zadowalająca. Kobiety, studentki pielęgniarstwa, mają świadomość zasad przeprowadzania badań profilaktycznych piersi, jednak nie zawsze te zasady stosują u siebie. Słowa kluczowe: profilaktyka, rak piersi Abstract Introduction: Cancer - both in Poland and in the world as a serious concern because of their prevalence. Every year breast cancer in Poland suffers from a growing number of women and according to the National Cancer Registry over the past three decades, the incidence of this type of cancer has more than doubled. Primary prevention of breast cancer is based primarily on raising health awareness on scientifically proven risk factors for breast cancer. The aim of the study was to assess the state of knowledge of women, nursing students, on the prevention of breast cancer. Material and methods: The study was conducted at the Faculty of Health Sciences University of Lublin. A total included 147 women students toward nursing, first and second degree. The research method was used diagnostic survey. The research material was collected using interview techniques, using a questionnaire by their own constructed based on a review of current literature. The statistical analysis of the collected material was performed in the package Statistica 10.0. StatSoft. Conclusion: Knowledge of the risk factors and symptoms of breast cancer among women, nursing students, is satisfactory. Women, nursing students, are aware of the principles of testing preventive breast, but not always, these rules apply at home. Key words: prevention, breast cancer